World Demand as a Determinant of Immiserizing Growth - Tamara Todorova (iBusiness, 2010)
Theoretically economic growth could have negative effects over the growing economy when production expands for products the world demand for which is inelastic. If growth occurs in sectors and for products the world demand for which is elastic it could be expected that total revenues to domestic producers and exporters increase. Our goal is to prove that growth would be immiserizing only for products for which world demand is inelastic and expansion leads to a sizable worsening of the terms of trade. We show that there are few such commodities, namely food products and natural resources such as oil. Studying econometrically the demand function for Brazilian coffee as an example, we compare our estimation of the elasticity of demand for Brazil's exports of green coffee with other research on the world elasticity of demand for green coffee. We conclude that for manufactured products the demand for which is highly elastic it is unlikely that exporting countries fall into immiserization, therefore, growth and further participation in global trade turn out to be quite beneficial. Our conclusion is that too much emphasis is put in economic theory and trade policy on the concept of immiserizing growth which is more of a theoretical possibility than a real-life problem.
Keywords: F12; F43; 330; Immiserizing growth; Terms of trade; Elasticity of demand; International trade